2021
DOI: 10.1021/acs.joc.1c00794
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic and Metal-Coordinated Confinement Effects Trigger Recognition and Selectivity

Abstract: We report the synthesis and characterization of a new water-soluble cavitand 1. The container features 2-aminobenzimidazole panels at the “rim” and pyridiniums at the “feet”. In the solid state, a single-crystal X-ray structure of the organic-soluble precursor 2 showed a stable vase form. The structure is stabilized by hydrogen-bonded bridges between adjacent panels through solvents and ions. In aqueous solution, binding of hydrophobic and amphiphilic guest molecules to 1 was investigated using 1H NMR. Alkanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Apparently, some form compression (folding or coiling) occurs with these methylenes near the open end of the cavitand to avoid exposure to water. A similar binding trend was observed in a Pd coordinated cavitand but different trends are seen in 2 and 3 [15,19,24] . In these cases, the polar end of the n ‐alkyl alcohols may be fixed by interactions with the upper‐rim imidazolone carbonyl groups.…”
Section: Resultssupporting
confidence: 62%
“…Apparently, some form compression (folding or coiling) occurs with these methylenes near the open end of the cavitand to avoid exposure to water. A similar binding trend was observed in a Pd coordinated cavitand but different trends are seen in 2 and 3 [15,19,24] . In these cases, the polar end of the n ‐alkyl alcohols may be fixed by interactions with the upper‐rim imidazolone carbonyl groups.…”
Section: Resultssupporting
confidence: 62%
“… [32] We recently expanded the applications of metal complexation by using 2‐aminobenzimidazoles for the walls of the cavitand (Figure 8 A). [33] The reorganized shape of the space in metallo‐cavitand H7−2Pd showed a good shape and size selectivity for o ‐difluorobenzene over its isomers. Competitive experiments concerning the binding of difluorobenzene isomers to cavitand H7−2Pd used 19 F NMR spectroscopy and revealed their stabilities decreased in the following order: o ‐difluorobenzene> p ‐difluorobenzene ≫ m ‐difluorobenzene (Figures 8 B, 8 C).…”
Section: Binding Selectivity In Water‐soluble Cavitandsmentioning
confidence: 95%
“…Many structural variants of cavitands have been reported that are based on the resorcinarene platform, with additional functional groups on the upper rim for further possibilities in selective guest recognition [32] . We recently expanded the applications of metal complexation by using 2‐aminobenzimidazoles for the walls of the cavitand (Figure 8A) [33] . The reorganized shape of the space in metallo‐cavitand H7−2Pd showed a good shape and size selectivity for o ‐difluorobenzene over its isomers.…”
Section: Binding Selectivity In Water‐soluble Cavitandsmentioning
confidence: 99%
“…Hydrogen bonding, and dispersive interactions are dependent on the surround environment and medium, that is, the type of solvent and their thermodynamic properties determine the strength of dispersive interactions. [18][19][20] Although most of the noncovalent interactions can be considered as electrostatic interactions on a single polarity scale, 21 the differences in the nature and strength of these interactions were computationally investigated using model systems which has improved our understanding of their binding affinity and selectivity. [22][23][24] Growing interest in crystal engineering and advent of noncovalent interactions in supramolecular assemblies lead to the popularity of cucurbituril for selective recognitions due to its ability to facilitate noncovalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Typical noncovalent interactions are weaker than the conventional covalent bonds, and their energetics are very sensitive to changes in the electronic or solvent environment around them. Hydrogen bonding, and dispersive interactions are dependent on the surround environment and medium, that is, the type of solvent and their thermodynamic properties determine the strength of dispersive interactions 18–20 . Although most of the noncovalent interactions can be considered as electrostatic interactions on a single polarity scale, 21 the differences in the nature and strength of these interactions were computationally investigated using model systems which has improved our understanding of their binding affinity and selectivity 22–24 .…”
Section: Introductionmentioning
confidence: 99%